Efficacy of video-music therapy on quality of life improvement in a group of patients with Alzheimer’s disease: a pre-post study - Rubbi, Ivan; Magnani, Daniela; Naldoni, Giada; Di Lorenzo, Rosaria; Cremonini, Valeria; Capucci, Patrizia; Artioli, Giovanna; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the study: Alzheimer’s disease is the most common degenerative dementia with a predominantly senile onset. The difficult management of altered behaviour related to this disorder, poorly responsive to pharmacological treatments, has stimulated growth in non-pharmacological interventions, such as music therapy, whose effectiveness has not been supported by the literature up to now. The aim of this study was to evaluate the efficacy of video-music therapy on quality of life improvement in Patients affected by Alzheimer’s Disease (AD). Methods: A pre-post study was conducted in a residential facility. 32 AD Patients, who attended this facility daily to participate in supportive and rehabilitative programs, were treated with 2 cycles of 6 video-music-therapy sessions, which consisted of folk music and video, recalling local traditions. In order to investigate their cognitive status, Mini Mental State Examination (MMSE) was administered and Patients were divided into stages according to MMSE scores. After each session of video-music-therapy, Quality of Life in Alzheimer’s Disease Scale (QOL-AD) was administered to our Patients. Results: 21 AD Patients completed the 2 cycles of video-music therapy. Among them, only the Patients with questionable, mild and moderate neurocognitive impairment (MMSE Stages 1, 2, 3) reported an improvement in their quality of life, whereas the Patients with severe deterioration (MMSE stage 4) did not report any change. Many items of QOL-AD improved, showing a statistically significantly correlation to each other. Conclusions: Video-music therapy was a valuable tool for improving the quality of life only in Patients affected by less severe neurocognitive impairment.